Oh, very young - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
I have Spore 100 in front of me and I would like to convey my personal thanks to the entire editorial team of Spore, writes Gaffoh Kpekpassi, an agricultural engineer from Togo, a self-professed keen reader of Spore.